ESSENTIAL OILS PHARMACOPEIALIDENTIFICATION TESTS AND USES - Mobeen Islam (Baqai Journal of Health Sciences)
Essential oils are recognized for their medicinal importance since ancient time and they continue to be of paramount significance, proved by the number of studies conducted in biological sciences in recent years. This review deals with the chromatographic techniques for the identification of essential oils, their components, and medicinal uses. The various identification tests for essential oils described in the British Pharmacopoeia (BP) involve physical, chemical, and chromatographic tests. The focus of this study is chromatographic techniques which are based on thin layer chromatography (TLC) and gas-liquid chromatography (GLC). The techniques are presented in a tabular form which mentions its chromatographic conditions like stationary phase, mobile phase, methods of detection and the compounds detected in different essential oils by these techniques. Silica gel is the most commonly used stationary phase in TLC whereas macrogol 20000, bonded macrogol 20000 or poly (dimethyl) (diethyl) siloxane supported on fused silica as a stationary phase is commonly used in GLC. The mobile phase in TLC varies from toluene to its combination with ethyl acetate or menthol in different ratios while the mobile phase in GLC is helium. The detection methods used for TLC are UV light and chemical reactions whereas the detector used in GLC is flame ionization. The components of essential oils identified by these techniques are up to 10 or more. Almost all essential oils possess antioxidant, anticancer, antimicrobial, anti-inflammatory and insect repellent properties along with other specific properties.